Pengembangan Sistem Deteksi Air Limbah Tekstil menggunakan Logika Fuzzy - Putra Berlian Ageng Mukti; Mochammad Hannats Hanafi Ichsan; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The textile industry continues to significantly contribute to the growth of the non-oil and gas sector and the national economy. The increasing production in the textile industry causes pollution to the environment because the results of large volumes of liquid wastewater are discharged into waters, both rivers and ditches. According to Badan Pusat Statistik (BPS), in 2020, the river water quality in Indonesia still needs improvement. To avoid this problem, the research will implement a system that can carry out monitoring to classify the status of textile wastewater. The system will use four input sensors for monitoring: a pH sensor for measuring pH, a DS18B20 sensor for measuring water temperature, an MQ135 sensor for measuring ammonia (NH3) gas, and a turbidity sensor for measuring water turbidity, which is processed on Arduino Mega 2560. The process wastewater classification uses fuzzy Mamdani logic for the decision-making process on the status of textile wastewater. The Mamdani fuzzy logic method is implemented with the Embedded Fuzzy Logic Library (eFLL) to apply fuzzification, inference, and defuzzification. The accuracy level of Mamdani's fuzzy logic is obtained by comparing the system output value of the research tool with the MATLAB output value, with an average water status accuracy of 99,67%. This result shows that the water classification process is magnificent.